Teaching writing by using Visual, Auditory, Read/Write, And Kinesthetic (VARK) learning style in descriptive text to the seventh grade students of SMPN 2 Jiwan - Ilham Nugroho Hanurawan (English Teaching Journal : A Journal of English Literature, Language and Education, 2017)
Writing is one of the English skills. Teaching writing is a process to improve students' ability to write in English correctly. Descriptive text is text used to describe a person, place or object. The difficulty experienced in teaching writing through descriptive text is the lack of attention of students towards the explanation given by the teacher. To overcome this, researchers applied VARK learning style to teaching writing. VARK learning style is a learning style using all five senses to get information or knowledge in the teaching and learning process. This study aims to explain the application of VARK learning style in teaching writing through descriptive text. The procedures for applying VARK learning style in teaching writing through descriptive text are: (1) The teacher explains the meaning, patterns and characteristics of descriptive text languages, (2) The teacher asks students to make small groups, (3) The teacher gives examples of descriptive texts, ( 4) The teacher gives questions in the form of pictures to students and asks to make descriptive texts, (5) The teacher asks students to show the results of students' work in front of the class. Based on this research, it can be seen that the advantages of VARK learning style is that it can increase student learning interest, student enthusiasm and reciprocity between teacher and students.